Financial Performance Of Islamic Banking After The Global Financial Crisis: A Comparison Between Islamic Commercial Banks And Islamic Business Unit Banks In Indonesia - Laili Rahmi (Ar-Raniry: International Journal of Islamic Studies, 2017)
The global financial crisis has affected some industries or non-industries around theworld. It has also impacted to Islamic banking in Indonesia, especially after 20072008. It has been recorded the Islamic banking industry in Indonesia shows a speedy recovery from the impact of the global financial crisis. Thus, this study aims to evaluate and examine the differences of Islamic banking’s financial performance after the global financial crisis in Indonesia. The financial performances in this study are profitability ratio (Return on Asset (ROA) and Return on Equity (ROE)), liquidity ratio (Financing to Deposit Ratio (FDR) and Current Asset Ratio (CAR)) and solvency risk ratio (Equity Multiplier (EM) and Debt to Equity Ratio (DER)). The samples in this study are the six Islamic banks from Islamic Commercial Banks (Bank Usaha Sharia (BUS)) and Islamic Business Unit Banks (Unit Usaha Sharia (UUS)) in Indonesia. Based on the results shows by the descriptive statistic, UUS is more effective in using their assets to generate income compared to BUS, but BUS is greater to manage their financing and more liquid than UUS whose has higher risk than BUS during 2009-2013. Independent sample t-test shows that there is significant difference in terms of profitability, liquidity and solvency risk ratio between BUS and UUS Indonesia during 2009-2013.